Partial purification and properties of glucosyltransferase from Streptomyces aureofaciens - Matĕjů, J; Cudlín, J; Steinerová, N; Blumauerová, M; Vanĕk, Z (Folia microbiologica, 1979)
Differential centrifugation, precipitation with ammonium sulphate and chromatography on DEAE-cellulose led to a twenty-fold purification of glucosyltransferase from Streptomyces aureofaciens B 96. The Michaelis constants for glucosyluridyl diphosphate (UDP-glucose) was 10.8 microM for 1,2-dihydroxy-9,10-anthraquinone (alizarin) 110 microM; the maximum rate of glucosylation reaction was 5.32 mumol per s per mg protein. The pH optimum was at 7.1; the flat temperature optimum was at 30 degrees C. Using some hydroxy derivatives of 9,10-anthraquinone it was found that the production of glucosides from aglycones with alpha-hydroxyl groups was about 1/8 of the values obtained with beta-hydroxyl substrates. In both types of aglycones the presence of another hydroxyl group led to a higher glucoside production.
Keywords: Glucosyltransferases; Uridine Diphosphate Glucose; glukosidy; glukosyltransferasy; uridindifosfátglukosa; Streptomyces aureofaciens; Anthraquinones; Glucosides; Hydrogen-Ion Concentration; Temperature; teplota; anthrachinony; koncentrace vodíkových iontů